The Association between Parental Support and Adolescents’ Psychological Complaints: The Mediating Role of a Good School Climate - Joacim Ramberg (Children, 2021)
Parental support is an important factor affecting young people’s mental well-being, but the school climate also plays an important role. However, few studies have previously examined whether the school climate serves as a mediator for adolescents’ mental health problems. This study aimed to investigate the association between parental support and students’ psychological complaints, while also examining the possible mediating role that a good school climate may have. Data derives from 5783 senior-level students (age 15–16) distributed over 152 school units in Stockholm municipality. Regression linear analysis was used for the analysis and Baron and Kenny’s four-step mediation model has been applied. Sobel’s test was conducted in order to test the significance of the mediation effect. The results show that there is a significant negative association between parental support and students’ psychological complaints, and that school climate has a mediating role in this association. It can be concluded that school climate has a partly mediating role in the association between parental support and students’ psychological complaints. Therefore, it seems important to develop the school climate in order to strengthen this source of support to reduce mental health problems among adolescents.